Enzimas e bactérias lignocelulolíticas do trato digestivo de larvas de Stenochironomus (Diptera:Chironomidae) - Koroiva, Ricardo (2011)
The presence of a lignocellulolytic enzyme complex and/or symbiotic microorganisms in the invertebrate guts is an indicative of its ability of using wood as energy source. Despite the microbial involvement in the cellulose digestive processes of some species of aquatic insects, there is a lack of information regarding the importance of microorganisms in the digestive capacity of chironomid larvae. This research focuses on the analysis of the activity of enzymes responsible for cellulose and hemicelluloses digestion and the cultivable bacterial community capable of hydrolyzing wood compounds in the digestive tract of Stenochironomus larvae Kieffer (Diptera, Chironomidae). This is a cosmopolitan genus characterized by mining larvae of submerged decaying branches. Two larval morphotypes were studied. The results of enzymatic analysis in the larval digestive tract, performed by quantification of reducing sugars, showed limited ability of both morphotypes in the degradation of cellulose, but indicated capacity to hydrolyze xylan. There were isolated thirty-one types of colonies during the characterization of bacterial communities, of which nineteen strain responded positively into the ability to hydrolyze at least one of the four substrates used as the main carbon source in the culture media. Degradation capability was assessed using colorimetric tests. The bacteria were classified using 16S rRNA gene analysis. No bacteria capable of degrading lignin were isolated. Pseudomonas was highly richness, Bacillus showed the greatest capacity for degrading different substrates and Sphingobium was present in both Stenochironomus morphotypes. The results obtained in this research emphasize the participation of microorganisms in the degradation of the wood consumed by the Stenochironomus larvae. This is the first report of lignocellulolytic bacteria and lignocellulolytic enzymes in the gut of wood-mining chironomid.